You Cannot Have the Cake and Eat It - How to Reconcile Liberal Fundamental Rights with Answers to the Climate Crisis - Lohse, Eva (2023)
Our Western-style constitutional systems are not only built on 16th to 18th century social contract theory, but also mainly on a liberal understanding of individual human rights. They are an element of constitutions and international treaties and are increasingly used as a basis for claims of individuals against states for more action to tackle the climate change crisis. However, a human right to a sustainable climate meets plenty of challenges if understood as a classic human right. The question is whether human rights offer a solution to legal questions of the climate crisis by empowering people to demand specific measures from states. The authors demonstrate how the search for solutions has altered the understanding of human rights globally and will continue to do so. It sheds a light on whether the premises on the relationship between state and individual and burdens on individual freedom can still be answered by paradigms from social contract theories and whether the social contract needs to be enlarged by including non-human actors (like eco-systems) or future generations.